(untitled) (New York, 2013)
The internal organisation and practices of operation of arbitral institutions are often not transparent and are rarely addressed in public discussions among arbitration practitioners. To shed some light on aspects of the internal organisation and operation of these institutions, ASA asked the MIDS (Geneva LLM in International Dispute Settlement) to conduct a broad survey of arbitral institutions based on a detailed questionnaire. The results are summarized in Chapter 1 of this volume. The further Chapters of this volume contain the presentations of the speakers at the ASA conference of 9 September 2011. They discuss responsibilities of the institutions in administering arbitration cases under their sets of rules in the different phases of an arbitral proceeding, from the constitution of the arbitral tribunal to supervision and quality control to financial aspects, such as cost control and the potential liability of arbitrators
Keywords: Arbitration and award, International.,Trọng tài thương mại quốc tế,Trọng tài và giải thưởng, quốc tế.,International commercial arbitration